Mencegah Second Victimization Melalui Asesmen Terpadu bagi Korban Penyalahgunaan Narkotika di Kabupaten Banyumas - Yusuf Saefudin; Gamalel Rifqi Samhudi (Universitas Muhammadiyah Purwokerto, 2021)
Cases of drugs abuse and illicit trafficking continue to rise along with the increasing number of addicts and abusers of narcotics. Addicts and Victims of Narcotics Abuse are often in a dilemma between the perpetrator or victim. Assessment integrated can clarify their position. The problems studied in this research is about how the concept of assessment integrated into the case of criminal acts of narcotics and how the mechanism of placement of victims of abuse of narcotics into institutions of rehabilitation. This research is a juridical-sociological, designed using survey method, observation, interview and literature study. The Data obtained were collected and analyzed qualitatively with the model of descriptive-analytical. Based on the results of research, assessment integrated designed to distinguish between addicts and victims of narcotics abuse with a drug dealer/courier narcotics. Assessment integrated to produce recommendations that contain a description of the involvement of the suspect with a network of illicit narcotics, the level of dependence on narcotics and a plan of rehabilitation of addicts and victims of narcotics abuse. Of the 15 cases studied, there were 8 cases of drug abuse and only 1 of 8 such cases that boil down to rehabilitation. The assessment integrated a mechanism that is able to avoid the victims of the abuse of narcotics from the threat of imprisonment. Avoiding the victims of drug abuse from a criminal to prison is expected to break the chain of problems of drug abuse and illicit trafficking. It can be realized through a pattern of different handling between the addict/abuser with a drug dealer/courier narcoticsKeywords: Integrated Assessment, the Narcotics Crime, the Victims of Drug Abuse